A Fractal which violates the Axiom of Determinacy - Riis, Søren (BRICS Report Series, 1994)
By use of the axiom of choice I construct a symmetrical and self-similar subset A \subseteq [0,1] \subseteq R. Then by an elementary strategy stealing argument it is shown that A is not determined. The (possible) existence of fractals like A clarifies the status of the controversial Axiom of Determinacy.